Administração pública e produção de água: um estudo comparativo da legislação sobre pagamento por serviços ambientais na Bacia Hidrográfica do Rio Grande - Flores, Nicole Mendes (2023)
The conception that maintaining capital accumulation is a guarantee of the prosperity of today's society highlights the main cognitive obstacle to understanding that the accumulative search is leading us to an environmental collapse. With natural resources becoming increasingly scarce, the Payment for Environmental Services (PES) mechanism emerges as a possibility for environmental management with the potential to preserve and increase the provision of environmental services. The objective of this study is to evaluate the environmental legislation of municipalities for the creation of municipal projects related to PES in the Rio Grande Hydrographic Basin (RGHB). As for the nature, this research is applied; From the point of view of obj ectives, the research has a descriptive character. Regarding technical procedures, it is a d ocumentary research whose objective was municipal laws, with a qualitative methodology being adopted for data analysis. As a technical product, a draft bill is presented aiming at the creation of municipal PES projects for the municipality of Poços de Caldas/MG. Only 80 of the 433 municipalities analyzed presented Ordinary Law regarding the PES and present projects aimed at maintaining water resources. The legislatio ns were analyzed under the topics of economic and financial sustainability, institutional arrangement and technical sustainability. The results indicate that municipal PES initiatives do not follow a standardization of arrangements, they are implemented in isolation and without coordination with the National PES Policy. The PES's focus solely as an economic mechanism has overshadowed the potential for promoting discussions on the use and conservation of water resources, with environmental education and awareness among users of environmental services being essential pillars for the perpetuity of this type of environmental public policy.